2014
DOI: 10.1111/medu.12512
|View full text |Cite
|
Sign up to set email alerts
|

Medical student depression, anxiety and distress outside North America: a systematic review

Abstract: Prevalences of psychological distress amongst medical students outside North America are substantial. Future research should move on from simple cross-sectional studies to better-quality longitudinal work which can identify both predictors for and outcomes of poor mental health in medical students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
265
6
40

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 368 publications
(333 citation statements)
references
References 41 publications
22
265
6
40
Order By: Relevance
“…This finding is in line of some studies, confirming medical studies as very stressful, from 20.9-90.0% of medical students experience stress, 7.7-65.5% anxiety, 6.0-66.5% depression [22][23][24].…”
Section: Discussionsupporting
confidence: 79%
“…This finding is in line of some studies, confirming medical studies as very stressful, from 20.9-90.0% of medical students experience stress, 7.7-65.5% anxiety, 6.0-66.5% depression [22][23][24].…”
Section: Discussionsupporting
confidence: 79%
“…(17) Previous studies have assessed the reliability and validity of Persian form of the GHQ-28 and were of acceptable ranges from 0.73 to 0.89. (18)(19)(20) Through factor analysis, the GHQ-28 has been divided into four subscales, which are somatic symptoms (items 1-7); anxiety/insomnia (items [8][9][10][11][12][13][14]; social dysfunction (items [15][16][17][18][19][20][21], and depression (items 22-28).…”
Section: Methodsmentioning
confidence: 99%
“…A systematic review on the prevalence of depression, anxiety and distress among medical students outside North America suggested that the rates of theses mental morbidities are remarkable. (13) A study in Vanderbilt University showed that anxiety and depression were more prevalent among medical students in comparison to other students of nonmedical disciplines and there were significantly higher rates of possibility of alcohol abuse and eating disorders. (14) Similar study in Iran reported that close to 50 percent of the medical students had ill mental health based on General Health Questionnaire (GHQ) score and there were significantly different scores due to age, gender and level of education.…”
Section: Introductionmentioning
confidence: 99%
“…Personal Problems (4,8,10) 73 (43.7%) of all students had experienced stressful life events and displayed troubles adjusting to them (Table 3). Latvian students adjusted worse to previous stressful life events than international students.…”
Section: Groupmentioning
confidence: 99%
“…Increased mental symptoms are often connected with increased somatic symptoms [1,2,3]. No consistent value for mental distress among medical students are present [4]. A previous research among the group of tested medical students suggests clinically relevant depressive symptoms among 23.5% [5].…”
Section: Introductionmentioning
confidence: 99%